2021
DOI: 10.1002/jia2.25693
|View full text |Cite
|
Sign up to set email alerts
|

Client and provider preferences for HIV care: Implications for implementing differentiated service delivery in Thailand

Abstract: Introduction: Differentiated service delivery (DSD) for antiretroviral therapy (ART) maintenance embodies the client-centred approach to tailor services to support people living with HIV in adhering to treatment and achieving viral suppression. We aimed to assess the preferences for HIV care and attitudes towards DSD for ART maintenance among ART clients and providers at healthcare facilities in Thailand. Methods: A cross-sectional study using self-administered questionnaires was conducted in September-Novembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Approximately 85% of clients received ART from facilitybased models, which were led by healthcare professionals and with MMD available. This finding coincides with our previous study, which found high preference for facility-based models over community-based models among ART clients in Thailand [17]. Only 3.6% and 2.7% of our clients received ART at the pharmacist-led pickup centers and KP-led CBOs, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Approximately 85% of clients received ART from facilitybased models, which were led by healthcare professionals and with MMD available. This finding coincides with our previous study, which found high preference for facility-based models over community-based models among ART clients in Thailand [17]. Only 3.6% and 2.7% of our clients received ART at the pharmacist-led pickup centers and KP-led CBOs, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Studies in Ghana and Zimbabwe suggest that the opportunity for comprehensive care and lower risk of inadvertent disclosure of HIV status due to the distance from home drove the preference for facility-based models among some PLHIV [18,24]. Thai people tend to trust and prefer receiving health services from healthcare professionals, particularly physicians, as they are perceived as more knowledgeable in a paternalistic healthcare system [17,25]. Some PLHIV in Thailand also feared social discrimination from disclosing their HIV status [26], which might make them want the sense of privacy and confidentiality of facility-based models over community-based models as well as individual models over group models.…”
Section: Discussionmentioning
confidence: 99%
“…While we found overall little difference in clinical outcomes for reduced visit frequency, there are other potential benefits of reduced visits, including decongestion of health facilities, reduced provider workload, prioritization of care for new or clinically unstable PLWH, and reduced transmission of COVID-19 in health centers [ 5 , 13 , 41 44 ]. Reducing visit frequency has been reported to be one of the easiest DSD models to implement and aligns strongly with the care preferences of PLWH by reducing the economic costs of attending frequent appointments, reducing stigma, and allowing PLWH to normalize HIV [ 3 , 4 , 10 , 11 , 45 , 46 ]. HIV services, however, need to remain flexible enough to accommodate return to facilities for those who opt back into standard care or when clinical requirements change [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our research adds to a growing body of knowledge around patient‐ and provider‐stated preferences for HIV prevention, counselling, testing, care and treatment [ 19 , 20 , 21 , 31 , 32 , 33 , 34 , 35 ]. Many studies focus on the clinical aspects of HIV care and treatment (viral load testing location and frequency, ART refill frequency, etc.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, providers endorsed the provision of support services, such as medication and appointment reminders; these are similar to our findings, though providers in our study preferred DOT over medication reminders alone, and accompanying clients or arranging transportation for clients over appointment reminders alone. Another study examined provider preferences for differentiated service delivery and ART maintenance services in Thailand, finding that providers endorsed longer ART refill visit spacing and the decentralization of ART maintenance services, as well as psychosocial support [ 32 ]. These findings align with our own; though many of these studies varied the frequency of services, such as viral load testing and ART refills, none explicitly varied the intensity of the service, and none included items specifically related to DOT.…”
Section: Discussionmentioning
confidence: 99%